The New Film History as Media Archaeology - Elsaesser, Thomas (Cinémas, 2004)
AbstractThe article assesses the impact of digital technologies on our understanding of film history. While the “New Film History” has revitalized the study of the cinema’s “origins,” it has not yet proven itself equally successful in analyzing the subsequent turn-of-the-century multi-media conjuncture. Faced with this challenge, the essay makes a case for a new historiographical model, “Media Archaeology,” in order to overcome the opposition between “old” and “new” media, destabilized in today’s media practice. The field of audio-visual experience needs to be re-mapped, clarifying what is meant by embodiment, interface, narrative, diegesis, and providing new impulses also for the study of non-entertainment uses of the audio-visual dispositif.